2012
DOI: 10.1111/j.1365-3040.2012.02588.x
|View full text |Cite
|
Sign up to set email alerts
|

Achieving yield gains in wheat

Abstract: Wheat provides 20% of calories and protein consumed by humans. Recent genetic gains are <1% per annum (p.a.), insufficient to meet future demand. The Wheat Yield Consortium brings expertise in photosynthesis, crop adaptation and genetics to a common breeding platform. Theory suggest radiation use efficiency (RUE) of wheat could be increased~50%; strategies include modifying specificity, catalytic rate and regulation of Rubisco, up-regulating Calvin cycle enzymes, introducing chloroplast CO2 concentrating mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
353
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 500 publications
(369 citation statements)
references
References 225 publications
(443 reference statements)
10
353
1
5
Order By: Relevance
“…Balancing biomass (source) with yield components (sink) through breeding While a number of studies have suggested that yield and radiation use efficiency can be increased by improving source and sink balance (Slafer and Savin 1994;Reynolds et al 2012), this is the first time the hypothesis has been tested in a realistic breeding context. Results indicate that selecting parents with high expression of biomass (source) and crossing to sources with good expression of sink traits (HI, KNO, TKW etc.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Balancing biomass (source) with yield components (sink) through breeding While a number of studies have suggested that yield and radiation use efficiency can be increased by improving source and sink balance (Slafer and Savin 1994;Reynolds et al 2012), this is the first time the hypothesis has been tested in a realistic breeding context. Results indicate that selecting parents with high expression of biomass (source) and crossing to sources with good expression of sink traits (HI, KNO, TKW etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, BM and HI are necessarily a function of genetically simpler traits which can be considered in greater detail when making more complex strategic crosses ( Fig. 1; Reynolds et al 2012). …”
Section: Pt Breeding Approach and Wider Breeding Objectivesmentioning
confidence: 99%
“…(1) Giymatly 2/17: relatively early headed and moderately resisistant to diseases; (2) Experiment was carried out with two variantscontrol and 25% Tilt treatment. Each genotype was grown with three replications.…”
Section: Methodsmentioning
confidence: 99%
“…The growth of productivity of major crops in recent years has decreased significantly [1]. Especially is apparent for wheat, the most important crop in the food security of the most regions of Eurasia, America and Australia [2]. In 2013, world production of wheat was 713 million tons, making it the third most-produced cereal after maize (1,016 million tons) and rice (745 million tons) [3].…”
mentioning
confidence: 99%
“…Wheat is the most important food crop of the world in terms of harvested area, trade value and human nutrition, having more influence on global food security than any other crop (Reynolds et al 2012). With current productivity increasing at a rate of about 1.1% per annum (Dixon et al 2009), or even stagnating in some regions (Brisson et al 2010), meeting the needs of a growing population with rising per capita consumption is a serious challenge.…”
Section: Introductionmentioning
confidence: 99%